Fatal liver failure associated with Valproate therapy in a patient with Friedreich's disease: review of Valproate hepatotoxicity in adults - König, Stephan A.; Schenk, M.; Sick, C.; Holm, Eggert; Heubner, C.; Weiss, A.; König, I.; Hehlmann, Rüdiger (Epilepsia, 1999)
Summary: Purpose: Valpróate (VPA)-associated hepatotoxicity is usually considered a problem of young children with polytherapy, mental retardation, and underlying metabolic defects. Methods: An adult patient with fatal liver failure during treatment with VPA is presented, and a review of the literature on other adult patients is given. Results: A 29-year-old female patient with Friedreich's ataxia and partial seizures with acute liver failure during VPA treatment is reported. The first symptoms of liver failure (i.e., apathy during febrile upper airway infection) occurred 2 months after starting VPA therapy. VPA was discontinued 10 days later on hospital admission, when she had hepatic encephalopathy and severe bleeding diathesis. The patient died of severe liver failure and bronchopneumonia after 4 weeks of supportive treatment. Conclusions: Twenty-six adult patients (>17 years) with VPA-associated fatal hepatotoxicity have been reported in the literature. Of the 26 adult patients, three were receiving VPA monotherapy. The age ranged between 17 and 62 years. The duration of VPA treatment before the first symptom varied between 7 days and 6 years. Twelve of the 26 affected adults had no underlying disease or a clearly nonmetabolic and non-hepatic disease. Therefore VPA-associated severe side effects also must be considered in adult patients without any evidence of a metabolic defect or underlying neurologic disease.
Issue online: 04 October 2006
Gesehen am 23.03.2022